ESR dosimetry with lithium, potassium, and sodium compounds. (March 2022) - Rech, Amanda B.; Kinoshita, Angela; Donate, Paulo M.; Baffa, Oswaldo
Abstract: This work consists of a first investigation of materials that could be used as ESR dosimeters with doses up to 5 Gy aiming possible applications that would include retrospective dosimetry or dosimetry in specific applications. The characteristics considered were radiological properties close to that of soft tissues, evaluated through their effective atomic number and mass attenuation coefficient, ESR signal dependence on the irradiation dose, sensitivity to dose in the range of ∼5 Gy when exposed to a 50 kV x-ray source and signal stability over a 30-day period. A total of 16 compounds of lithium, potassium and sodium were analyzed, including the already known dosimeter material, lithium formate. Among them, lithium carbonate, lithium phosphate, sodium formate, sodium acetate, sodium citrate, sodium dithionite, sodium carbonate, showed eligible characteristics. After analyzing the ESR dose-response curves, the molecules that showed greater sensitivity to radiation in descending order are: sodium formate, sodium acetate, sodium citrate and sodium dithionite, however, lower than lithium formate. Sodium formate and sodium citrate presented ESR signals with high stability, similar to lithium formate, with fading of ∼3% in 30 days, different from sodium acetate, which showed a 19% reduction. Sodium citrate also presents radiological properties close to soft tissue. Therefore, considering all properties, in the set of the new materials studied in this work, sodium citrate is a promising material for ESR dosimetry. Highlights: EPR spectra study of Li, Na and K compounds were compared to lithium formate, for low energy x-rays. Seven compounds showed relation between ESR signal and absorbed dose, minimum detectable dose was estimated. These compounds present the possibility to improve the dose evaluation in accident scenarios with components of daily use.